2015
DOI: 10.1159/000371350
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Modulates the Immune System and Improves Atopic Dermatitis in Children

Abstract: Background: Vitamin D seems to influence the evolution of atopic dermatitis (AD) in children. Methods: We tested the vitamin D serum levels of 39 children with AD (AD group t₀) and of 20 nonallergic healthy controls (C group). AD severity was evaluated using the AD scoring system (SCORAD index). Cytokine serum levels (IL-2, IL-4, IL-6, IFN-γ, TNF-α) and atopy biomarkers were also measured. The patients were then treated with vitamin D oral supplementation of 1,000 IU/day (25 mg/day) for 3 months. We then reeva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 29 publications
3
58
0
9
Order By: Relevance
“…Two studies [29,30] enrolled pediatric patients who had a history of AD, and both studies showed that eczema area and severity index (EASI) was decreased after calcidiol supplementation. Similar findings were shown by the others [9,22,27,28] but with using the SCORAD.…”
Section: Groupsupporting
confidence: 91%
See 2 more Smart Citations
“…Two studies [29,30] enrolled pediatric patients who had a history of AD, and both studies showed that eczema area and severity index (EASI) was decreased after calcidiol supplementation. Similar findings were shown by the others [9,22,27,28] but with using the SCORAD.…”
Section: Groupsupporting
confidence: 91%
“…The consistency of such a finding in a large number of studies [5][6][7][17][18][19][20][21][22], confirms that the low level of calcidiol in such a disease is not a coincidence, and that calcidiol deficiency has a possible role in the pathogenesis of AD. The controversy in the serum level of calcidiol in AD patients is mainly viewed among adult AD patients, where several studies showed the non-significant alteration of calcidiol levels among patient and control groups [8,9].…”
Section: Groupsupporting
confidence: 55%
See 1 more Smart Citation
“…Many clinical trials including their meta-analysis have shown that vitamin D supplementation results in significant improvement in AD severity (measured by SCORAD and Eczema Area and Severity Index) [121,135,136,137,138]. Di Filippo et al [138] suggested that vitamin D supplementation exerts its positive effect on AD by normalizing the altered Th1 and Th2 cytokines like IL-2, IL-4, IL-6, and IFN-γ in AD patients. In another study, Drozdenko et al [139] showed that the oral intake of vitamin D increases the frequencies of CD38+ B cells to enhance the B-cell receptor-mediated response and decreases the IFN-γ and IL-17 T-cell cytokine response in vitamin D-deficient individuals.…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Current treatment recommendations include the liberal use of emollients, wet-wrap therapy, vitamin D supplementation, topical calcineurin inhibitors, and topical corticosteroids (TCS) [1,33,34] . When moisturizers alone are not sufficient to control the itch and inflammation, TCS are the mainstay of treatment for AD.…”
mentioning
confidence: 99%